Geography of food production in Social Studies: socio-environmental conflicts in Osa, Costa Rica in the period 2013-2017 - Zuñiga Villalobos, Dylan (2021)
Introduction  The transformations in the Social Studies' curriculum encourage the use of geospatial technologies. However, their employment for the investigation of the subject has been recent and they have been hardly addressed in the classrooms. Objective The main objective of this article is to propose the elaboration of geographic information among secondary school students and teachers, by using the WEB MAP SERVICE tool of the National System of Territorial Information (SNIT), as well as the Geographical Atlas of the Costa Rican Technological Institute (TEC). Method The selected method is the documentary analysis of academic studies, newspaper articles, and census information that problematize food production in the territory of Osa between 2013 and 2017, within the framework of the socio-environmental conflict produced by the project of the PINDECO concessionaire (Del Monte) that intended to plant pineapple near the Térraba-Sierpe Wetland. Results The results allowed the elaboration of three infographics to teach the didactic unit "Geography of food production", using Canva platform on mobile devices with internet access and QR codes. Conclusions The use of geospatial information technologies (GIT) can be operationalized through socio-educational research models of action.